Variation in Networks and Forms of Support for Care‐Seeking Across the HIV Care Continuum in the Rural Southeastern United States. Issue 1 (14th March 2017) - Hill, Miranda; Huff, Amber; Chumbler, Neale
Abstract: Purpose: In spite of progress in understanding the importance of social support for health outcomes in Persons Living with HIV (PLWH), more remains to be known about mechanisms of support most beneficial at each stage of HIV treatment. In this study, we use a qualitative analytic approach to investigate the forms and sources of social support deemed most integral to the diagnosis, care engagement, and medication adherence behaviors of a diverse sample of PLWH in a mostly rural health district in the Southeastern United States. Methods: In‐depth interviews (N = 18) were collected during the qualitative phase of a larger mixed methods needs assessment for the Northeast Georgia Health District. A deductive‐inductive analysis of participant narratives revealed variation in the perceived importance of particular forms and sources of social support during the initial versus advanced stages of HIV care. Findings: PLWH identified the emotional, informational, and appraisal support provided by family as especially critical for emotional stability, coping, and care linkage during the initial stages of diagnosis and treatment. However, once in care, PLWH emphasized informational and instrumental forms of support from care providers and appraisal support from peers as key influences in care engagement and retention behaviors. Conclusion: Increased understanding of the social support mechanisms that contribute to the HIV treatment behaviors of PLWH can fill knowledge gaps in research and inform the efforts of health care providers seeking to leverage various aspects of the social support toward improving the care retention, health, and wellness outcomes of PLWH.